2017
DOI: 10.1186/s12864-017-3824-1
|View full text |Cite
|
Sign up to set email alerts
|

Differences in responses of grass carp to different types of grass carp reovirus (GCRV) and the mechanism of hemorrhage revealed by transcriptome sequencing

Abstract: BackgroundGrass carp is an important farmed fish in China that is affected by serious disease, especially hemorrhagic disease caused by grass carp reovirus (GCRV). The mechanism underlying the hemorrhagic symptoms in infected fish remains to be elucidated. Although GCRV can be divided into three distinct subtypes, differences in the pathogenesis and host immune responses to the different subtypes are still unclear. The aim of this study was to provide a comprehensive insight into the grass carp response to dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
35
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 66 publications
(38 citation statements)
references
References 42 publications
3
35
0
Order By: Relevance
“…Similar expression pattern was also observed in other pro-apoptotic genes in grass carp [19,32]. Moreover, the dynamic changes of GCRV copy number in infected grass carp was detected in our previously study [33]. Results showed that the relative copy number of GCRV (type II GCRV) was extremely low in 1 and 3 days postinfection, followed by a dramatic increase in 5 days post stimulation and a slight reduction in 7 days post infection.…”
Section: Discussionsupporting
confidence: 82%
“…Similar expression pattern was also observed in other pro-apoptotic genes in grass carp [19,32]. Moreover, the dynamic changes of GCRV copy number in infected grass carp was detected in our previously study [33]. Results showed that the relative copy number of GCRV (type II GCRV) was extremely low in 1 and 3 days postinfection, followed by a dramatic increase in 5 days post stimulation and a slight reduction in 7 days post infection.…”
Section: Discussionsupporting
confidence: 82%
“…Therefore, the six miRNAs that were downregulated may suggest that their target genes upregulated after GCRV infection. Interestingly, we also revealed the overactivity of the complement cascade and immune inflammatory response in grass carp after GCRV infection in our previous study, which is the reason for hemorrhagic symptoms in infected grass carp leading to death [ 40 ]. These results therefore suggest that an mRNA–miRNA–circRNA network is present in grass carp following GCRV infection, providing new insight into the mechanisms underlying GCRV.…”
Section: Discussionmentioning
confidence: 91%
“…However, because of its large with a long reproductive cycle, it is hard to study the antiviral mechanisms in the grass carp in vivo (Lin et al, 2019). CIK cells can be infected by GCRV, and this infection is characterized by the systematic induction of a mild host immune response, involving a variety of classical antiviral signal transduction pathways (Ji et al, 2018;Yu et al, 2017;He et al, 2017). In our previous study, CIK cells were used to study the RNA expression patterns in response to viral infection, including circRNAs, mRNAs, and miRNAs.…”
Section: Discussionmentioning
confidence: 99%